2011
DOI: 10.3141/2250-01
|View full text |Cite
|
Sign up to set email alerts
|

Detection Distances to Crosswalk Markings

Abstract: The objective of this study was to investigate the relative daytime and nighttime visibility of three crosswalk marking patterns (transverse lines, continental markings, and bar pairs). In general, this study collected information on the distance from the crosswalk when the participant verbally indicated its presence. The 78 participants were about evenly divided between male and female groups and between younger (<55 years) and older (≥55 years) groups. The study was conducted with instrumented vehicles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Crosswalks marked with paint are the safer places to cross a street because they are visible to drivers. When the marking patterns are zebra crossings, the degree of identification by drivers increases compared to other marking patterns such as bar pairs or transverse lines (Fitzpatrick et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Crosswalks marked with paint are the safer places to cross a street because they are visible to drivers. When the marking patterns are zebra crossings, the degree of identification by drivers increases compared to other marking patterns such as bar pairs or transverse lines (Fitzpatrick et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Given that only one site was included in the model, the estimated effect could be because of site-specific factors rather than the continental marking. Given that other studies show differences in driver behavior and preferences given crosswalk markings, additional data on this marking type would be helpful to explore this issue more thoroughly ( 38 , 39 ).…”
Section: Model Results and Discussionmentioning
confidence: 99%
“…Visibility: The literature provides clear evidence that HVCs are more visible to both drivers and pedestrians compared with basic markings. Fitzpatrick et al’s rigorous 2010 field visibility study found that drivers detect continental (i.e., longitudinal) markings at a midblock crossing at about “twice the distance upstream as the transverse markings during daytime conditions.” Daytime detection distance was longer than nighttime ( 2 ). It is not well established how or whether the increased visibility translates to effectiveness (e.g., reduced crashes or increased driver yielding), but in the absence of more definitive information, increased visibility intuitively seems to make for a more effective marking.…”
Section: Introductionmentioning
confidence: 97%
“…Associated treatments: Many other studies have reported increased effectiveness associated with HVCs but only in conjunction with other treatments—including illuminated overhead signs and pedestrian refuge islands ( 2, 3, 913 ).…”
Section: Introductionmentioning
confidence: 99%